Finding Social and Environmental Justice in the Fashion Production Chain in Brazil: When Fashion is Created with Nature by Women in Their Communities - Evelise Anicet Rüthschilling; Eloisa Artuso (International Journal for Crime, Justice and Social Democracy, 2022)
Brazil covers a large territory, and although only 15% of its population is distributed in rural areas (IBGE Educa 2015), rural dwellers take on the chief responsibility for conserving local biodiversity. This article uses empirical research with a qualitative approach to present four cases of consolidated communities working with Amazonian rubber, regenerative cotton, weaving and lacework. It shows how rural communities pursue solutions for sustainable livelihoods in their own place of origin through the production of raw materials and products for the fashion chain, ensuring food security, income generation, maintenance of local biomes and gender justice. Particularly, this study examines the role of women beyond their families in ensuring work equity and better income distribution. Design appears as a positive agent, transforming ancestral and artisanal culture and knowledge into product innovation with added value to ensure production viability as well as enhancing community wellbeing.